2007
DOI: 10.1536/ihj.48.215
|View full text |Cite
|
Sign up to set email alerts
|

Superior Logistic Model for Decay of Ca2+ Transient and Isometric Relaxation Force Curve in Rabbit and Mouse Papillary Muscles

Abstract: SUMMARYA decrease in myocardial intracellular calcium concentration ([Ca 2+ ] i ) precedes relaxation, and a monoexponential function is typically used for fitting the decay of the Ca 2+ transient. However, a logistic function has been shown to be a better fit for the relaxation force curve, compared to the conventional monoexponential function. In the present study, we compared the logistic and monoexponential functions for fitting the [Ca 2+ ] i declines, which were measured using the aequorin meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Furthermore, we have shown that the decay for myocardial Ca 2+ transient at 30 8C also shows the half-logistic characterization (Mizuno et al 2007). Computer simulation of Ca 2+ handling and CB kinetics has also shown that the cumulative CB detachment curve is reasonably fit by the logistic function (Sakamoto et al 1996).…”
Section: Logistic Modelmentioning
confidence: 80%
“…Furthermore, we have shown that the decay for myocardial Ca 2+ transient at 30 8C also shows the half-logistic characterization (Mizuno et al 2007). Computer simulation of Ca 2+ handling and CB kinetics has also shown that the cumulative CB detachment curve is reasonably fit by the logistic function (Sakamoto et al 1996).…”
Section: Logistic Modelmentioning
confidence: 80%
“…For example, τ E for the CaT decline curve in mouse myocytes is reported to be lower than that in rabbit myocytes [29]. We have also found that τ L and τ E for the CaT decline curve in mouse are smaller than those in rabbit [35]. In the mouse myocyte, the peak increase in L-type Ca 2+ current is smaller, and the SR Ca 2+ content, SR Ca 2+ -ATPase activity, and outward Na + -Ca 2+ exchanger current are greater than in the rabbit myocyte [28,29].…”
Section: Species Differences In Calcium Transientmentioning
confidence: 45%
“…It has recently been shown, however, that the half-logistic function fits the falling phase of CaT more precisely than the mono-exponential function does [35]. Thus the half-logistic time constant (τ L ) may be superior as an index of velocity to the conventional mono-exponential time constant (τ E ) [35]. Similarly, we suppose that the half-logistic function could fit the rising phase of CaT from the beginning of twitch stimulation to dCa/dt max more precisely than the mono-exponential function.…”
Section: Calculated Value Rabbit Mousementioning
confidence: 97%
See 1 more Smart Citation
“…The experimental procedures have been previously described in detail [4,6,7]. In short, seven albino rabbits (Japan White; body weight 2.0-2.5 kg) and 15 mice (C57BL/6; body weight 25-30 g) were anesthetized with intravenous (1.5-2.0 mg/kg) and intraperitoneal (15-20 mg/kg) pentobarbital sodium, respectively.…”
Section: Surgical Preparationmentioning
confidence: 99%